Speech Function in Teaching Speaking Skill: Evaluation, Analysis, and Recommendation - Muhamad Taridi; Wahyuni Fitria; Supriusman Supriusman; Revini Deska (Indonesian Journal of EFL and Linguistics, 2022)
This study aims to assess and analyse the sorts of speech functions used by teachers in the tenth grade at one vocational high school in Jambi, Indonesia, and to identify the most prevalent kind. The study was carried out using descriptive qualitative research and descriptive analysis design. In this study, data were triangulated through observation and documentation. The study's targets were English teachers, and the transcribed data was divided into three categories of language functions. Holmes' concept is applied to classify speech functions. There are three types of utterance functions: expressive, imperative, and referential. The results showed that out of 60 speech functions, the directive function was applied by instructors the most frequently, accounting for 31 of them (51.66%). Directive one is the main reason, as it delivers interaction by directing and requesting the student. The study recommends that there are still many types of speech functions, but alternatively, directives are more prominent. Other researchers can gather data from many sources, including Instagram's English-language account, an English newspaper or magazine, and many more. The current study encourages English as a Foreign Language (EFL) teachers to complete a task and determine an assignment for future research. Given the implications of directive functions for English teachers in teaching speaking skills and the ability to inquire about something and command and request learners to perform something.